Ideology in Thompson’s, Kailey’s, and Robbin-Coker’s collections of poems: A psychoanalytical exploration - Thulla, Philip Foday Yamba; Fofanah, Ibrahim Mustapha (Journal of Research on English and Language Learning (J-REaLL), 2024)
This study employed psychoanalytic theory to delve into the ways Sierra Leonean poets Celia Eva Beatrice Thompson, Princess Mildred Kailey, and Kayode Adesimi Robbin-Coker explored themes of despair, lust, and loss in their poetry. Addressing a notable gap in literary criticism, especially regarding Sierra Leonean authors, the research sought to raise the international stature of African writers and support students facing challenges with poetry in West African public exams. Employing psychoanalytic principles, the study uncovered deeper meanings behind the unconscious drives and emotions in these poets' works. It involved analyzing the occurrence of themes, detecting psychoanalytically significant lines and phrases, and identifying central themes and literary techniques used to express complex emotions. The analysis, which combined thematic and literary analysis, focused on the language, themes, and use of figurative language, diction, and other poetic devices in Thompson’s 41, Kailey’s 20, and Robbin-Coker’s 23 poems. This approach highlighted their distinct ways of depicting despair, lust, and loss. By integrating thematic analysis, the study offered a more profound comprehension of each poet's style. Ultimately, this psychoanalytic exploration aimed to enhance critical interpretation skills and helped in understanding the deeper psychological aspects of Sierra Leonean and other African poetry.